Chaperones vs. oxidative stress in the pathobiology of ischemic stroke - Soldatov, Vladislav; Venediktov, Artem; Belykh, Andrei; Piavchenko, Gennadii; Naimzada, Mukhammad David; Ogneva, Nastasya; Kartashkina, Natalia; Bushueva, Olga (Frontiers in Molecular Neuroscience, 2024)
As many proteins prioritize functionality over constancy of structure, a proteome is the shortest stave in the Liebig's barrel of cell sustainability. In this regard, both prokaryotes and eukaryotes possess abundant machinery supporting the quality of the proteome in healthy and stressful conditions. This machinery, namely chaperones, assists in folding, refolding, and the utilization of client proteins. The functions of chaperones are especially important for brain cells, which are highly sophisticated in terms of structural and functional organization. Molecular chaperones are known to exert beneficial effects in many brain diseases including one of the most threatening and widespread brain pathologies, ischemic stroke. However, whether and how they exert the antioxidant defense in stroke remains unclear. Herein, we discuss the chaperones shown to fight oxidative stress and the mechanisms of their antioxidant action. In ischemic stroke, during intense production of free radicals, molecular chaperones preserve the proteome by interacting with oxidized proteins, regulating imbalanced mitochondrial function, and directly fighting oxidative stress. For instance, cells recruit Hsp60 and Hsp70 to provide proper folding of newly synthesized proteins—these factors are required for early ischemic response and to refold damaged polypeptides. Additionally, Hsp70 upregulates some dedicated antioxidant pathways such as FOXO3 signaling. Small HSPs decrease oxidative stress via attenuation of mitochondrial function through their involvement in the regulation of Nrf- (Hsp22), Akt and Hippo (Hsp27) signaling pathways as well as mitophagy (Hsp27, Hsp22). A similar function has also been proposed for the Sigma-1 receptor, contributing to the regulation of mitochondrial function. Some chaperones can prevent excessive formation of reactive oxygen species whereas Hsp90 is suggested to be responsible for pro-oxidant effects in ischemic stroke. Finally, heat-resistant obscure proteins (Hero) are able to shield client proteins, thus preventing their possible over oxidation.